2003
DOI: 10.1542/peds.111.5.e604
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Referral to a Single Encopresis Clinic Over 20 Years

Abstract: ABSTRACT. Objective. To compare the characteristics of children with encopresis referred to a single encopresis clinic over the course of 20 years, including symptoms, previous diagnostic and therapeutic interventions, and parental attitudes.Methods. A retrospective study was conducted of an encopresis clinic at a tertiary care pediatric hospital. Questionnaires at initial evaluation elicited information about bowel habits, soiling, previous evaluations, previous treatments, and parental attitudes.Results. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…It was reported that the risk of defacation problems is high in the future in children whose mothers experience anxiety and depression during the period of the child's toilet education (2). It was stated that a part of children with encopresis might not have taken, might have refused or forgotten the treatment reccomended at the first presentation and the attitude of the families on this subject should be examined (22). In some studies, it was reported that encopresis might be considered as a psychosomatic disorder (23), marriage problems were observed frequently in families of children with psychosomatic symptoms and physical symptoms played a role in distracting the family from conflict and in providing the balance of the family (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the risk of defacation problems is high in the future in children whose mothers experience anxiety and depression during the period of the child's toilet education (2). It was stated that a part of children with encopresis might not have taken, might have refused or forgotten the treatment reccomended at the first presentation and the attitude of the families on this subject should be examined (22). In some studies, it was reported that encopresis might be considered as a psychosomatic disorder (23), marriage problems were observed frequently in families of children with psychosomatic symptoms and physical symptoms played a role in distracting the family from conflict and in providing the balance of the family (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Since encopresis is a disorder which may lead to distress in the whole family, it may be considered that marriage problems occur related to the disruption of the family's general functionality by encopresis symptoms. However, it has been reported in the literature that familial factors prevent treatment compliance and play a role in maintenance of the symptoms (20,22). Because of high risk of comorbidity and chronicity and insufficiency of behavioral treatment methods in many cases the significance of family focused approaches has been emphasized (27).…”
Section: Discussionmentioning
confidence: 99%
“…Fishman, Rappaport, Schonwald, and Nurko (2003) found medications and regular sitting times to be the most common encopresis management strategies used by providers. Eighteen to 23% of patients, however, reported that a specialty referral was made without first receiving encopresis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of children with chronic constipation show reduced frequency of bowel movements in combination with fecal incontinence; passage of large stools that clog the toilet; hard stools; painful defecation; stool-withholding behavior; stool toileting refusal; and large stools in the rectum, palpable on abdominal or rectal examination [11,[23][24][25]. Rectoanal examination often reveals perianal feces [3].…”
Section: Symptomatologymentioning
confidence: 99%
“…Fecal incontinence in a child triggers a lot of parental stress because of dishonesty of the child about their fecal accidents [52] and the burden of cleaning clothes [6]. The majority of the parents assume that fecal incontinence is caused by the child's laziness, carelessness and stubbornness [24]. Furthermore, parents are imposed by a heightened awareness of bowel function, prompting their incontinent child to toilet more frequently than parents of children without fecal incontinence [53].…”
Section: 22mentioning
confidence: 99%